PER «COLMARE UNA LACUNA» SENTITISSIMA - Luisa Spagnoli (Bollettino della Società Geografica Italiana)
The considerations that the text intends to develop don’t pretend to propose a systematic study of Italian geographical thought, but rather considers the problematic matter of private publishing, without going into the critical surveys that have characterized (Italian) geographical literature. The paper intends to analyze the history of the development of the Italian Historical Atlas project in order to understand the principal phases that had the greatest impact in its process, focusing on the intentions and aspirations of those who, in large part, were directly involved in such a plan. The geographers and historians involved had different roles and varying influence over the time of the project’s progression. Even though some carelessness evident within the most recent historiography has omitted a return to the subject – except during the last few decades – the geographical debate had been even more «silent», without offering any critical reflections on the matter, despite its important involvement predominantly at the beginning of the project.